If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + 4 = 13x + -2 Reorder the terms: 4 + 11x = 13x + -2 Reorder the terms: 4 + 11x = -2 + 13x Solving 4 + 11x = -2 + 13x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13x' to each side of the equation. 4 + 11x + -13x = -2 + 13x + -13x Combine like terms: 11x + -13x = -2x 4 + -2x = -2 + 13x + -13x Combine like terms: 13x + -13x = 0 4 + -2x = -2 + 0 4 + -2x = -2 Add '-4' to each side of the equation. 4 + -4 + -2x = -2 + -4 Combine like terms: 4 + -4 = 0 0 + -2x = -2 + -4 -2x = -2 + -4 Combine like terms: -2 + -4 = -6 -2x = -6 Divide each side by '-2'. x = 3 Simplifying x = 3
| 4x+17y=13 | | 2sinx-3cosx-2.5=0 | | 2(3x-1)-3(x+1)=0 | | 3x-2y-3z+7x-5y+9z= | | (x-34)= | | 6-x=3-4 | | a*3=15 | | (P-4)(2)=16 | | 4n^2+12n=160 | | 7x(2)-6=57 | | 4(x+3)=5x+3 | | 15=8x+7 | | -5qr*(-7pr^3)= | | 20x+7=127 | | 4x(2)-6=74 | | 4n^2-7=249 | | M(2)+7=6 | | 6x^2-5=481 | | B(2)=34 | | A(2)+1=2 | | 8km^2p*3mn^3= | | 3n^2-10=17 | | X(2)=29 | | 3x-4y+2z+5x+2y-3z= | | R(2)=96 | | 2cd*cd= | | 4x+3+8-3x=-2x+6x-2 | | 30x+4=244 | | 3p^2+10=310 | | 4hk*5st= | | 3mn*9m= | | 2,5/x=8/3 |